Mesenchymal Stem Cell-derived Exosomes: Novel Therapeutic Approach for Inflammatory Bowel Diseases - Cheng-mei Tian; Mei-feng Yang; Hao-ming Xu; Min-zheng Zhu; Yuan Zhang; Jun Yao; Li-sheng Wang; Yu-jie Liang; De-feng Li (Hindawi Limited, 2023)
As double membrane-encapsulated nanovesicles (30-150 nm), exosomes (Exos) shuttle between different cells to mediate intercellular communication and transport active cargoes of paracrine factors. The anti-inflammatory and immunomodulatory activities of mesenchymal stem cell (MSC)-derived Exos (MSC-Exos) provide a rationale for novel cell-free therapies for inflammatory bowel disease (IBD). Growing evidence has shown that MSC-Exos can be a potential candidate for treating IBD. In the present review, we summarized the most critical advances in the properties of MSC-Exos, provided the research progress of MSC-Exos in treating IBD, and discussed the molecular mechanisms underlying these effects. Collectively, MSC-Exos had great potential for cell-free therapy in IBD. However, further studies are required to understand the full dimensions of the complex Exo system and how to optimize its effects.